Outcomes of 847 childhood-onset systemic lupus erythematosus patients in three age groups - Lopes, S. R.M.; Gormezano, N. W.S.; Gomes, R. C.; Aikawa, N. E.; Pereira, R. M.R.; Terreri, M. T.; Magalhães, C. S. [UNESP]; Ferreira, J. C.; Okuda, E. M.; Sakamoto, A. P.; Sallum, A. M.E.; Appenzeller, S.; et al. (SAGE Publications, 2017)
Objective The objective of this study was to assess outcomes of childhood systemic lupus erythematosus (cSLE) in three different age groups evaluated at last visit: group A early-onset disease (<6 years), group B school age (≥6 and <12 years) and group C adolescent (≥12 and <18 years). Methods An observational cohort study was performed in ten pediatric rheumatology centers, including 847 cSLE patients. Results Group A had 39 (4%), B 395 (47%) and C 413 (49%). Median disease duration was significantly higher in group A compared to groups B and C (8.3 (0.1-23.4) vs 6.2 (0-17) vs 3.3 (0-14.6) years, p < 0.0001). The median Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SLICC/ACR-DI) (0 (0-9) vs 0 (0-6) vs 0 (0-7), p = 0.065) was comparable in the three groups. Further analysis of organ/system damage revealed that frequencies of neuropsychiatric (21% vs 10% vs 7%, p = 0.007), skin (10% vs 1% vs 3%, p = 0.002) and peripheral vascular involvements (5% vs 3% vs 0.3%, p = 0.008) were more often observed in group A compared to groups B and C. Frequencies of severe cumulative lupus manifestations such as nephritis, thrombocytopenia, and autoimmune hemolytic anemia were similar in all groups (p > 0.05). Mortality rate was significantly higher in group A compared to groups B and C (15% vs 10% vs 6%, p = 0.028). Out of 69 deaths, 33/69 (48%) occurred within the first two years after diagnosis. Infections accounted for 54/69 (78%) of the deaths and 38/54 (70%) had concomitant disease activity. Conclusions This large multicenter study provided evidence that early-onset cSLE group had distinct outcomes. This group was characterized by higher mortality rate and neuropsychiatric/vascular/skin organ damage in spite of comparable frequencies of severe cumulative lupus manifestations. We also identified that overall death in cSLE patients was an early event mainly attributed to infection associated with disease activity.
Keywords: Childhood-onset systemic lupus erythematosus; death; mortality and cumulative damage; nephritis; outcome